Uji Kinerja Mesin Pengiris Bahan Baku Kerupuk Dengan Mekanisme Gerak Translasi Menggunakan Pisau Rotasi Vertikal Kapasitas 60 Kg/Jam - Eko Daskiro; Franky Sutrisno; Nurdiana Nurdiana; Zulkifli Lubis; Mahyunis Mahyunis; Eswanto Eswanto (Fakultas Teknik UMSU, 2018)
On the slicing machine for raw material for crackers performance test to analyze the effect of speed rotation to the results of slicing crackers which aims to get slicing speed to get productivity and the quality of slicing good raw crackers, and maximum incision capacity. In the analysis of shaft rotation on the results of slicing the raw material of crackers the material used (machine for slicing crackers raw material). Then do the operation or slicing activity of the crackers raw material in three variations, namely at 40 rpm rotation), the results of the slicing of crackers as much as 90.9 kg / hr with 630.6 kw, and at 30 rpm rotation, and the material slicing results obtained. raw crackers were 72.2 kg / hr and power 613.3 kw and at 20 rpm rotation the results of slicing crackers as much as 55.8 kg / hr were obtained with a power of 68 kw. After three rounds of rotation at 40 rpm were carried out, the highest slicing capacity and the best quality were obtained, so the higher the speed, the more raw material for sliced crackers.